EDUCAÇÃO AMBIENTAL NA ZONA RURAL: UMA ANÁLISE A PARTIR DE UMA ESCOLA NO INTERIOR DO MUNICÍPIO DE VITÓRIA DAS MISSÕES/RS - Tolfo, Viviane do Nascimento Bueno (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2011)
Environmental education is a right to the entire Brazilian population and should be available bothin formal and informal education. Thus, the work in question aims to investigate whether thisteaching is actually being offered in basic education schools for this, a survey was conducted in aschool inside the city of Victory Mission / RS to verify if the environmental education is present inthe same school and if so how the faculty has developed the theme with the students. We alsosought to discover if the school has already put some specific project with the environment, andwith teachers, how they view their own knowledge on the subject. For these goals could beachieved, there was the application of questionnaires to teachers of the school studied and also aninterview with the director of it. Therefore, it was found that environmental education is actuallybeing offered in school, as she has already developed their own projects on the topic.